STUDI KESIAPAN PENGETAHUAN WARGA SEKOLAH DALAM MENGHADAPI BENCANA GEMPA DAN TSUNAMI DI KOTA PADANG (Studi Kasus SMK Negeri 5 Padang) - 301-308 , Fajar Suhengki (Universitas Negeri Padang, 2014)
ABSTRACT This research is a descriptive study aimed to obtain a picture of the school readiness of citizens SMK 5 Padang in the face of the earthquake and tsunami. readiness are examined include: 1) preparedness, 2) early warning, 3) mitigation.Population in this study were residents of the school SMK Negeri 5 Padang are 1,457 people’sand 304 samples are used as people’s, the sampling technique stratified random sampling. The type of data used is survey data obtained from a questionnaire distributed to the school community. Samples were classified according to their profession that is teacher, student and supporting staff. Data analysis techniques performed by descriptive statistical analysis using the percentage formula then described in narrative form. Based on the results of data analysis has been conducted, obtained most of the students, teachers, and supporting staffare very ready for all indicator’s. Keywords: Preparedness, Early warning, Mitigation